The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0006-87052011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Respostas de cultivares de algodão ao cloreto de mepiquat aplicado via embebição de sementes

Abstract: ResumoAs recomendações de reguladores de crescimento cloreto de mepiquat (CM) geralmente não consideram as diferenças entre cultivares de algodoeiro utilizadas para o cultivo. O trabalho teve como objetivo avaliar o crescimento e o desenvolvimento de cultivares de algodão ante a embebição das sementes com regulador de crescimento cloreto de mepiquat, visando à sua caracterização quanto à resposta ao tratamento. Foram utilizadas as cultivares IPR-120, IAC-24, CD-405, Delta Opal e Fibermax 966, cujas sementes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a recent study, Almeida & Rosolem (2012) observed that the application of MC to cotton seeds decreased shoot length, but had no significant effect on dry matter production, root length, shoot:root ratio or leaf area:root length ratio. However, Nagashima et al (2011) concluded that cotton seeds treated with MC decreased shoot dry matter by 62%, while the leaf area decreased 52%.…”
Section: Characteristicmentioning
confidence: 98%
“…In a recent study, Almeida & Rosolem (2012) observed that the application of MC to cotton seeds decreased shoot length, but had no significant effect on dry matter production, root length, shoot:root ratio or leaf area:root length ratio. However, Nagashima et al (2011) concluded that cotton seeds treated with MC decreased shoot dry matter by 62%, while the leaf area decreased 52%.…”
Section: Characteristicmentioning
confidence: 98%